Hypomethylation of the c-myc promoter region induced by phenobarbital in rat liver - Katarzyna Urbanek-Olejnik; Monika Liszewska; Alicja Winczura; Agnieszka Hernik; Paweł Struciński; Jan K. Ludwicki (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. The changes in DNA methylation are considered as one of the early events in hepatocarcinogenesis. Objective. We evaluated the ability of phenobarbital (PB) - the most widely used anticonvulsant worldwide and classical rodent liver carcinogen - to cause the promoter region of the c-myc protooncogene hypomethylation as well as changes of mRNA level of this gene. Moreover, the expression of Dnmt1 protein in rat treated with this compound was analyzed. Material and Methods. Male Wistar rats received PB in daily oral doses of 92.8 mg kg-1 b.w. day-1 (at 24-h intervals; for one, three and fourteen days). Methylation of the c-myc promoter region was measured by PCR-based methylationsensitive restriction enzyme analysis (MSRA). Levels of mRNA for c-myc and protein Dnmt1 were assayed using Real-Time PCR and Western Blot, respectively. Results. The study showed that phenobarbital stimulated persistent changes in DNA methylation, i.e. loss of methylation in the promoter region of the c-myc gene and up-regulated its mRNA level. In addition, a significant increase in protein level of Dnmt1 in the c-myc over-expressing liver cells was observed. Conclusion. The oppose relationship between Dnmt1 activity and methylation status of c-myc gene was demonstrated. The c-myc over-expression by demethylation might represent an important, early events in the mechanism of action (MOA) of phenobarbital.